Clinical impact of patient adherence to a fixed-dose combination of olmesartan, amlodipine and hydrochlorothiazide - Bramlage, Peter; Ketelhut, Reinhard; Fronk, Eva-Maria; Wolf, Wolf-Peter; Smolnik, Ruediger; Zemmrich, Claudia; Schmieder, Roland (Clinical Drug Investigation, 2014)
Recent findings from randomized clinical trials indicate an improved patient adherence and blood pressure (BP) control by using fixed-dose combinations (FDCs) in the treatment of hypertension. The aim of the present study was to verify those data in a large real-world sample of hypertensive patients and to cross-check adherence evaluation performed by physicians and patients self-assessment.A European multi-center, prospective, 24-week, non-interventional study was conducted including 14,979 patients with essential hypertension and new treatment with olmesartan, amlodipine and hydrochlorothiazide as an FDC. Patients' adherence was measured using the Morisky Medication Adherence Scale (MMAS-8) and a non-standardized questionnaire was used by physicians and patients for self-assessment.The mean age of the patients was 63.9 ± 11.78 years and 46.5 % were women. One or more cardiovascular risk factors were present in 71.9 % of patients and 94.7 % had been treated for hypertension before study entry. Mean adherence to medication by MMAS-8 improved from 6.0 to 6.9 at study end. Corresponding improvements of adherence were seen on physicians' and patients' self-assessments throughout the study. Mean decrease of systolic/diastolic BP was 26.4/12.8 mmHg without a relevant difference between the MMAS-8 adherence levels. BP target achievement improved from 55.3 to 67.7 % in patients with low versus high adherence. The overall rate of patients with adverse drug reactions was very low (1.76 %) but more frequent in patients with low adherence.Our data confirm previous clinical trial data on the improvement of medication adherence by switching antihypertensive combination therapy to an FDC and a subsequent improvement in BP target achievement. An observed trend toward a reduction in adverse drug reactions needs to be further investigated in clinical trials.
EVALuna2:3678